Safety of Carotid Revascularization in Patients With a History of Coronary Heart Disease. Issue 2 (February 2019) - Volkers, Eline J.; Algra, Ale; Kappelle, L. Jaap; Becquemin, Jean-Pierre; de Borst, Gert J.; Brown, Martin M.; Bulbulia, Richard; Calvet, David; Eckstein, Hans-Henning; Fraedrich, Gustav; Gregson, John; Halliday, Alison; et al.
Abstract : Background and Purpose—: We investigated whether procedural stroke or death risk of carotid artery stenting (CAS) compared with carotid endarterectomy (CEA) is different in patients with and without history of coronary heart disease (CHD) and whether the treatment-specific impact of age differs. Methods—: We combined individual patient data of 4754 patients with symptomatic carotid stenosis from 4 randomized trials (EVA-3S [Endarterectomy Versus Angioplasty in Patients With Symptomatic Severe Carotid Stenosis], SPACE [Stent-Protected Angioplasty Versus Carotid Endarterectomy], ICSS [International Carotid Stenting Study], and CREST [Carotid Revascularization Endarterectomy Versus Stenting Trial]). Procedural risk was defined as any stroke or death ⩽30 days after treatment. We compared procedural risk between both treatments with Cox regression analysis, stratified by history of CHD and age (<70, 70–74, ≥75 years). History of CHD included myocardial infarction, angina, or coronary revascularization. Results—: One thousand two hundred ninety-three (28%) patients had history of CHD. Procedural stroke or death risk was higher in patients with history of CHD. Procedural risk in patients treated with CAS compared with CEA was consistent in patients with history of CHD (8.3% versus 4.6%; hazard ratio [HR], 1.96; 95% CI, 0.67–5.73) and in those without (6.9% versus 3.6%; HR, 1.93; 95% CI, 1.40–2.65; P interaction =0.89). In patients with history of CHD, procedural risk was significantly higher after CAS compared with CEA in patients aged ≥75 (CAS-to-CEA HR, 2.78; 95% CI, 1.32–5.85), but not in patients aged <70 (HR, 1.71; 95% CI, 0.79–3.71) and 70 to 74 years (HR, 1.09; 95% CI, 0.45–2.65). In contrast, in patients without history of CHD, procedural risk after CAS was higher in patients aged 70 to 74 (HR, 3.62; 95% CI, 1.80–7.29) and ≥75 years (HR, 2.64; 95% CI, 1.52–4.59), but equal in patients aged <70 years (HR, 1.05; 95% CI, 0.63–1.73; 3-way P interaction =0.09). Conclusions—: History of CHD does not modify procedural stroke or death risk of CAS compared with CEA. CAS might be as safe as CEA in patients with history of CHD aged <75 years, whereas for patients without history of CHD, risk after CAS compared with CEA was only equal in those aged <70 years. Abstract : Supplemental Digital Content is available in the text.